Atomic layer etchings of transition metal dichalcogenides with post healing procedures: equivalent selective etching of 2D crystal hetero-structures. (19th June 2017) - Chen, Kuan-Chao; Chu, Tung-Wei; Wu, Chong-Rong; Lee, Si-Chen; Lin, Shih-Yen
Abstract: The atomic layer etchings of molybdenum disulfide (MoS2 ) and tungsten disulfide (WS2 ) are demonstrated in this paper. By using the oxygen plasma etching and the following re-sulfurization procedures, a mono-layer MoS2 sample with an enhanced photoluminescence intensity is obtained from the sample originally with bi-layer MoS2, which suggests that atomic layer etching of MoS2 can be achieved and the following re-sulfurization procedure can recover the partially oxidized MoS2 remained on the substrate back to a complete MoS2 film. By repeating oxygen plasma etchings and a final re-sulfurization procedure, multi-layer WS2 can be selectively etched off from the WS2 /MoS2 hetero-structure. A top-gate WS2 /MoS2 hetero-structure transistor is fabricated with source/drain electrodes contacted directly to the MoS2 channel by using the repeated atomic layer etching technique. The results have revealed that the equivalent selective etching effect for 2D crystal hetero-structures can be achieved by repeating the atomic layer etching procedure, which is an important step for the device fabrication of 2D crystal hetero-structures.